Studi Etnobotani Jahe (Zingiber officinale) pada Masyarakat Desa Banyior Kecamatan Sepulu Kabupaten Bangkalan - Husnul Hotimah; Ari Hayati; Hasan Zayadi (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2019)
Ginger (Zingiber officinale) is a plant belonging to the Rhizoma group, ginger plants are relatively easy to find and its use has expanded not only for cooking purposes, but also for health, Ginger or commonly called "Jheih" in Madura is a plant that has often been used by the Banyior community as food or traditional medicine or more commonly called jamu or "jhemoh" in the Maduran language. In general, drinking herbs which are formulated from plants has become the habit of Maduran families and communities. This study aims to determine the public perception of the benefits of Ginger plants in the Banyior Village, Sepulu District, Bangkalan Regency. This study uses descriptive exploratory methods which include: literature studies, field observations, interviews, data analysis, and documentation of the distribution of ginger plants. The results of this study indicate the potential of Ginger plants in Banyior Village as food ingredients 54%, and as traditional medicine 46%. The ginger plant parts that are used are 38% leaves, 50% rhizomes, 12% stems. The number of ginger found was 7 clusters in Sabungan Hamlet and 6 clumps in Lenden Hamlet